Penerapan Metode Diskusi untuk Meningkatkan Hasil Belajar PAI Kelas IV SDN 06 Ampang Gadang - Yuetri, Yuetri (EduSpirit : Jurnal Pendidikan Kolaboratif, 2024)
This study aims to improve students’ learning outcomes in Islamic Religious Education (PAI) by using group discussion methods and audiovisual media in the 4th grade of SDN 06 Ampang Gadang. This research utilizes the Classroom Action Research (CAR) approach, consisting of two cycles. In cycle I, the student mastery rate reached 62.5%, while in cycle II, the mastery rate increased to 93.75%. This improvement indicates the effectiveness of the group discussion method with audiovisual media in enhancing students’ understanding of PAI materials, particularly in analyzing Q.S. Al-Hujurat verse 13 and Hadith about diversity. Observations of student activity also show an increase in student involvement and interaction during the learning process.